“The Wandering Nerve Linking Heart and Mind” – The Complementary Role of Transcutaneous Vagus Nerve Stimulation in Modulating Neuro-Cardiovascular and Cognitive Performance - Dolphin, Helena; Dukelow, Tim; Finucane, Ciaran; Commins, Sean; McElwaine, Paul; Kennelly, Sean P. (Frontiers in Neuroscience, 2022)
The vagus nerve is the longest nerve in the human body, providing afferent information about visceral sensation, integrity and somatic sensations to the CNS via brainstem nuclei to subcortical and cortical structures. Its efferent arm influences GI motility and secretion, cardiac ionotropy, chonotropy and heart rate variability, blood pressure responses, bronchoconstriction and modulates gag and cough responses via palatine and pharyngeal innervation. Vagus nerve stimulation has been utilised as a successful treatment for intractable epilepsy and treatment-resistant depression, and new non-invasive transcutaneous (t-VNS) devices offer equivalent therapeutic potential as invasive devices without the surgical risks. tVNS offers exciting potential as a therapeutic intervention in cognitive decline and aging populations, classically affected by reduced cerebral perfusion by modulating both limbic and frontal cortical structures, regulating cerebral perfusion and improving parasympathetic modulation of the cardiovascular system. In this review article we summarise the research to date investigating the cognitive effects of VNS therapy, and its effects on neurocardiovascular stability.